Dampak Modal Sosial dan Literasi Keuangan terhadap Inklusi Keuangan BUMDes di Kabupaten Gorontalo - Kayla Az Zahra Abd. Latief; Herlina Rasjid; Srie Isnawaty Pakaya (BADAN PENERBIT STIEPARI PRESS, 2026)
This research is motivated by the importance of Village-Owned Enterprises (BUMDes) as drivers of the village economy, in accordance with Permendesa PDTT Number 4 of 2015, which aims to improve community welfare through the management of assets, services, and businesses. However, many BUMDes face obstacles such as the low quality of human resources managers, a lack of understanding of financial literacy among the community, and sub-optimal relations with the village government, which cause many BUMDes to be inactive or not yet contribute significantly. In Gorontalo Regency, out of 191 BUMDes in 2020, 61 had not yet reported financial administration due to the managers' lack of capability. Transparent, accountable, and sustainable financial management of BUMDes requires adequate financial literacy. In addition, social capital in the form of traditions, networks, and trust in rural areas plays an important role in driving BUMDes economic activities and realizing welfare and poverty alleviation. Although the financial literacy rate in Gorontalo society reached 49.68% in 2022, there is still a gap with financial inclusion, which reached 85.10%. Therefore, this study aims to analyze the impact of social capital and financial literacy on the financial inclusion of BUMDes in Gorontalo Regency.